2008
DOI: 10.1021/ic8016326
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Fragmentation of Polyoxotungstate Anions

Abstract: A series of phospho-polyoxotungstate anions was transferred to the gas phase via electrospray ionization (ESI), and the anions' fragmentation was examined by collision-induced dissociation (CID). The anions included [PW12O40]3-, [P2W18O62]6-, and {Co4(H2O)2][PW9O34]2}10- as well as lacunary and metal-substituted derivatives such as [PW11O39]7- and [MPW11O39]5- (M = Co(II), Ni(II), Cu(II)). Common species observed in the mass spectra arose from protonation and alkali metal cationization of the precursor ions. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 51 publications
0
35
0
1
Order By: Relevance
“…Although a few systematic studies of the gas-phase fragmentation of POM clusters have been reported so far [12,[20][21][22], little attention has been paid to the interaction between the cations and the POM anions in the gas phase, which reflects intrinsic nature of interaction between these two entities. The interaction is simple in the case of alkali metal cations (i.e., Na + , K + , etc).…”
mentioning
confidence: 99%
“…Although a few systematic studies of the gas-phase fragmentation of POM clusters have been reported so far [12,[20][21][22], little attention has been paid to the interaction between the cations and the POM anions in the gas phase, which reflects intrinsic nature of interaction between these two entities. The interaction is simple in the case of alkali metal cations (i.e., Na + , K + , etc).…”
mentioning
confidence: 99%
“…The larger energy gap between α and γ isomers for tungsten-rich POM may inhibit isomerization into and fragmentation from the γ-Keggin structure. This likely explains the preferential formation of the M 6 O 19 2-Lindqvist anion, which is known to be the most abundant fragmentation product of the α isomer of W 12 POM [31].…”
Section: Structural Isomers Of Keggin Anionsmentioning
confidence: 98%
“…In the present study, we use a straightforward method of preparing mixed addenda Keggin POMs, PMo 12-n W n O 40 3-(n = 0-12), for analysis by electrospray ionization mass spectrometry (ESI-MS) and examine their dissociation pathways and relative stability towards fragmentation by means of collision-induced dissociation (CID) experiments. A few groups have previously studied the Keggin Mo 12 POM, W 12 POM, and selected mixed addenda POMs employing CID to analyze fragmentation patterns of the respective species [27][28][29][30][31][32]. However, to the best of our knowledge, there are no prior reports of systematic atom-by-atom CID studies of the full range of mixed addenda Keggin POMs.…”
mentioning
confidence: 99%
“…By electrospray ionization mass spectrometry of aqueous tungstate solutions, Walanda et al [12] showed some peaks as multiply charged W 12 species; however, those peaks were of such low abundance and such poor resolution that their composition remained ambiguous. Recently, using ESI-MS, Ma et al [15] unambiguously assigned gas-phase Keggin-type structures to phosphotungstate species with 12 or 18 tungsten atoms. However, these researchers did not work with tungsten compounds without heteroatoms.…”
Section: Spectra Recorded From Aqueous Analyte-derived Spotsmentioning
confidence: 99%
“…As a consequence to this low signal-to-noise ratio, an unambiguous assignment of a chemical formula to an ion, based on isotope cluster determinations, appeared less reliable. In a more recent ESI-MS report by Ma et al [15], possible structures for gas-phase phosphotungstate fragments, and charge assignments to tungsten species have been discussed on the basis of isotopic peak separations. They also carried out MS-MS analysis on phosphotungstate species, and some important neutral losses that take place were identified.…”
mentioning
confidence: 99%